2001
DOI: 10.1002/ijc.1427
|View full text |Cite
|
Sign up to set email alerts
|

2-benzoxazolyl and 2-benzimidazolyl hydrazones derived from 2-acetylpyridine: A novel class of antitumor agents

Abstract: Here we describe the effects of novel benzoxazol-2-yl and benzimidazol-2-yl hydrazones derived from 2-pyridinecarbaldehyde and 2-acetylpyridine. The IC 50 values for inhibition of cell proliferation in KB-3-1, CCRF-CEM, Burkitt's lymphoma, HT-29, HeLa, ZR-75 and MEXF276L by most of the novel compounds are in the nanomolar range. In colony-forming assays with human tumor xenografts the compounds 2-actylpyridine benzoxazol-2-ylhydrazone (EPH52), 2-acetylpyridine benzoimidazol-2-ylhydrazone (EPH61) and 2-acetylpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 19 publications
0
68
0
1
Order By: Relevance
“…[10] Recent modifications to the ligands have resulted in higher antitumor activity, as well as lower toxicity towards normal cells. [11] A related factor regarding the structure of the ligands is the stability of their copper complexes, as delivery of copper to the target cells can be hampered by sequestering agents that mediate copper trafficking in biological systems. The chelating nature of thiosemicarbazones allow them to strongly bind the copper ions, and it is reasonable to expect that ligands that give rise to highly stable tridentate chelates behave in a similar fashion.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Recent modifications to the ligands have resulted in higher antitumor activity, as well as lower toxicity towards normal cells. [11] A related factor regarding the structure of the ligands is the stability of their copper complexes, as delivery of copper to the target cells can be hampered by sequestering agents that mediate copper trafficking in biological systems. The chelating nature of thiosemicarbazones allow them to strongly bind the copper ions, and it is reasonable to expect that ligands that give rise to highly stable tridentate chelates behave in a similar fashion.…”
Section: Introductionmentioning
confidence: 99%
“…25 A second known target for HCTs is topoisomerase IIα (Topo IIα) an enzyme which controls the DNA topology during cell division by inducing temporary double strand breaks. 26,27,28,29 A series of Topo IIα inhibiting HCTs showed high affinity for the enzymes ATP binding pocket, thus acting as catalytic inhibitor of Topo IIα without the generation of DNA double strand breaks. 30 Although the structureactivity relationships (SARs) for HCTs Topo IIα inhibition are far from being completely understood, it was suggested that reaction with copper(II) leading to square-planar complexes enhances the Topo IIα inhibition rate significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of acylhydrazones the presence of the carbonyl oxygen atom promotes the formation of a chelate binding center [3]. Hydrazones and their metal complexes possess pronounced biological and pharmaceutical activities as antitumor [5][6][7], antimicrobial [8], antituberculosis [9] and antimalarial agents [10]. Hydrazones play an important role in improving the antitumor selectivity and toxicity profile of antitumor agents by forming drug carrier systems employing suitable carrier proteins [11].…”
Section: Introductionmentioning
confidence: 99%